Curriculum design based on competencies for the open and distance systems: creation of a Master’s degree in Food Security (Revista Electrónica Calidad en la Educación Superior, 2018)
Ensuring food security is a global problem, so the need arose to create an educational program that will contribute to the generation and management of knowledge on food security from a panoptic and international vision, able to become actual intervention projects and collaborative and transdisciplinary global cooperation projects promoting the involvement of intersectoral levels, governmental or private and, above all, generating collaborative projects. Therefore, from the action research process, a proposal based on the Open and Distance University, systems was developed for a curriculum design under the socio-formative competence approach for a master’s degree program in food security, using as data sources an extensive literature review, other relevant documents, open interviews, an anecdotal record and the discussion group technique. It is expected that implementing this curriculum design will result in training professionals capable of generating actions to alleviate hunger and promote rural development.